Developing Interactive Learning Media of “Venn Gram” to Improve Conceptual Understanding of Set Operations - Fadhanila Syainuralita Prillyana; Hendarto Cahyono; Anis Farida Jamil (MEJ (Mathematics Education Journal), 2020)
This research aimed at discovering the validity and effectiveness of the interactive media of "Venn Gram" to improve the conceptual understanding of the set operations. This research was a development research (research and development). The research subjects were the students of 7th grade who consisted of nine students. The data collection techniques were in the form of a validation questionnaire and test. The subjects were in the form of pre-test and post-test questions which later the answer sheets were used as an increase of students' conceptual understanding before and after using the media. The validation questionnaire results showed that 84% of the media were very valid, 83% of the material was very valid, and 82% of the test questions were very valid. The test results found that seven students experienced an increase in the pre-test and post-test scores. Meanwhile, two other students experienced a decrease. The results of students who had increased showed that the ability of students in understanding the concept of set operations was included in the high criteria before and after using the media. The media of the Venn Gram can be used to improve the conceptual understanding of set operations.